Uso de evidências em políticas educacionais - o contexto internacional e o quadro brasileiro - Ana Luiza Machado De Codes; Herton Ellery Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Evidence-based education policymaking has been prevalent in many countries today. Brazil is part of this picture. In countries that have followed this trajectory for a long time, recent discussions point to the need to recalibrate, in some dimensions, this way of making policies. Issues such as budgeting and knowledge incorporation resulting from school practices come to the fore. And Brazil, how is it going in this process? It is the point explored in this text. The Brazilian context is analyzed here in terms of the structure and maturation of procedures and practices. The discussion tries to apprehend the "degree" of the country along this journey, relying upon three fundamental approaches, which explain the use of evidence in the formulation of educational policies: i) the technical-functional perspective, focused on learning outcomes (skills, cognitive knowledge, and analytical capacity); ii) sociopolitical, which deals with cultural and attitudinal issues; and iii) institutional or organizational, associated with the idea of values. The study points out that Brazil demonstrates notable progress, especially concerning the legal and institutional framework built so far. However, it is necessary to advance further so that the evidence knowledge transforms and enriches the educational reality accordingly - mainly in terms of culture and management.
Keywords: I28; 330; evidence-based educational policies; public policy making; brazilian educational policies; performance evaluation; promotion of equality